Assessing satisfaction level among car purchaser in Malaysia empirical study of Perodua Sabah region / Faerozh Madli - Madli, Faerozh (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
The primary objective of this study is to obtain the factors contribute to the decrease of sales performance in context of PERODUA for Sabah region. The study was conducted from the currently news, data of sales performance, and data of customer satisfaction of PERODUA. It is give inspiration for researcher to study to obtain the data from the lenses of the PERODUA customer. For this purpose, 322 questionnaires were distributed, of which return in fully and very usable for data analysis. Survey results indicate that most of the customers not satisfy with elements of the price of PERODUA. This figure should enough for the management of PERODUA for investigate and research deeply for future marketing plan. The taken action was very important to make the PERODUA can compete very well in market and directly deliver better service that is from context of service and product to the customer.